Association between nitrate exposure in groundwater and its health risk among residents in Machang district, Kelantan - Nik Yahaya, Nik Muhamad Azraie; Mohd Sham, Shaharuddin; Abidin, Zaenal; Sholehhudin, Mochammad (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Nitrate (NO3-) in groundwater originates from natural sources or human-made activities, including agriculture and industries. Anthropological activities can contribute to a substantial increase and may lead to health problems, such as methemoglobinaemia. The purpose of this research was to identify the level of nitrate in groundwater in villages located near paddy fields and to ascertain health risk towards residents. Methods: This research was carried out in January 2020 involving three villages in Machang district in Kelantan state, located north-east of Peninsular Malaysia. A total of 74 respondents were recruited with an equal number of wells studied. Nitrate levels were identified using the Hanna Instrument multi-meter with the nitrate electrode attached. Age, depth of wells and distance from paddy fields were also recorded. Weight of respondents was measured to calculate the hazard quotient related to nitrate exposure. Results: Nitrate levels in groundwater did not exceed the maximum limit of 10 mg/L set by health authorities. It ranged from 0.56 to 6.58 mg/L with a mean ± SD of 2.25±1.26 mg/L. Most wells were more than 20 years old (83.78%) and more than 15m deep (44.59%). Distance from paddy fields ranged from 3 – 150 m with a mean ± SD of 73.78±38.82 m. Level of nitrate between sampling sites were not significantly different (p > 0.05). The same goes for other variables (p > 0.05). Conclusion: Hazard Quotient for all residents was less than 1 (HQ < 1), as they were exposed to low levels of nitrate.